Teaching English through Literature: Little House in the Big Woods - Giyatmi, G; Wijayava, Ratih; Arumi, Sihindun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Teaching language, in this case is English, through literature is not a new phenomenon. However there are still debates on it. Meanwhile the language teacher should be able to find interesting ways to teach English. Due to the communicative competence target of teaching language, teaching English through literature can be one of alternative that can be used in the class. It is because literature provides the learners with authentic language materials that are good to improve the learners’ communicative competence. Having read the novel entitles Little House in the Big Woods written by Laura Ingalls Wilder, the writers realized that there are many elements, especially the cultural elements, that can be brought to the class for teaching English. So the writers would like to explain the cultural elements in that novel that can be used in teaching English and what language skills can be taught by those cultural elements. This research hopefully can be an inspiration to teach English in the class by using literature especially novel.This is a descriptive research. The data of this research are cultural elements found in Little House in the Big Woods and the data source is Laura Ingalls Wilder’s novel entitles Little House in the Big Woods. The technique for collecting data is documentation with content analysis. The cultural elements found in the novel are geographical condition, tradition, belief, and social values. The results show that the cultural elements on the novel can be used as material for teaching vocabulary (geographical situation, tradition), English language skills such as listening, speaking, reading, and writing. The genre of the text for teaching the language skills can be in the form of descriptive text (tradition that deals with needle work and belief that deals with religion and folklore) and procedure text (tradition that deals with how to cook). Besides, it can be used to teach culture through Cross Culture Understanding with social value materials (speaking manner, eating manner, and meeting person manner)